Redesign User Interface Dan User Experience Aplikasi Any.Do Menggunakan Metode Design Thinking - Cicih Cicih (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
As part of the final project for the Independent Study Certified Campus Merdeka program, we developed a prototype of the Any.do application through a redesign effort by applying the Design Thinking methodology. This project integrated various aspects of sustainable design into the User Interface (UI) and User Experience (UX), aligning them with user needs as well as environmentally-conscious business objectives. The primary aim of this final project was to explain the features and functionalities of the application that can contribute positively to environmental sustainability and create a more intuitive and user-friendly UI/UX experience. The evaluation results demonstrated positive feedback from users regarding the design improvements and the overall enhanced quality of the application experience.